2010
DOI: 10.1186/1471-2202-11-131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aversive odour presentation on inhibitory control in the Stroop colour-word interference task

Abstract: BackgroundDue to the unique neural projections of the olfactory system, odours have the ability to directly influence affective processes. Furthermore, it has been shown that emotional states can influence various non-emotional cognitive tasks, such as memory and planning. However, the link between emotional and cognitive processes is still not fully understood. The present study used the olfactory pathway to induce a negative emotional state in humans to investigate its effect on inhibitory control performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…A novel finding was that odors affected emotional arousal ratings in an interactive way; specifically, the rated arousal of happy faces was lower in the unpleasant odor condition compared to the pleasant odor condition, perhaps suggesting an olfactory inhibition of incongruent emotional signals from the face stimuli. Such effects have been found for aversive odors in the Stroop task ( Finkelmeyer et al, 2010 ). Our work partly replicates previous research findings for arousal ratings, such as Cook et al (2017) , however, this effect was not significant for disgusted expressions.…”
Section: Discussionmentioning
confidence: 58%
“…A novel finding was that odors affected emotional arousal ratings in an interactive way; specifically, the rated arousal of happy faces was lower in the unpleasant odor condition compared to the pleasant odor condition, perhaps suggesting an olfactory inhibition of incongruent emotional signals from the face stimuli. Such effects have been found for aversive odors in the Stroop task ( Finkelmeyer et al, 2010 ). Our work partly replicates previous research findings for arousal ratings, such as Cook et al (2017) , however, this effect was not significant for disgusted expressions.…”
Section: Discussionmentioning
confidence: 58%
“…The current results suggest that these ORs may be related to anti-fatigue effects. Finkelmeyer et al [ 49 ] reported that the presentation of the neutral odorant had no effect on task performance and an aversive odorant condition which induces negative emotional state was found to reduce the reaction times for incongruent stimuli of the Stroop color-word interference task only in comparison with an air control condition. The authors concluded that this difference was observed because participants experienced temporary positive emotion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (Delplanque et al, 2017;Seubert et al, 2017), olfactory stimuli could induce a positive (or negative) emotional state. Colognes could induce a positive emotional state (Schiffman et al, 1995), whereas hydrogen sulfide might induce an unpleasant one (Finkelmeyer et al, 2010). In addition, citrus coniferous scents usually make people feel tense and hostile, whereas floral woody scents usually make people feel relaxed (Retiveau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%